Case report: rheumatoid arthritis complicated by chronic myelogenous leukemia treated with interferon - Abe, T; Imai, K; Tokunoh, T; Yawata, A; Sasaki, S; Hayashi, T; Kurokawa, S; Matsunaga, T; Sakai, H; Ishida, T (Nihon Rinshō Menʾeki Gakkai kaishi, 1995)
A fifty-six-year old man complained of arthralgia and swelling of both feet, morning stiffness in both hands and finger joints in March 1987, and was treated with non-steroidal anti-inflammatory agents at another hospital. He has been treated for chronic myelogenous leukemia (CML) since May 1990. He was admitted to our hospital in March 1991 because of worsening of his multiple arthralgias, and a diagnosis of rheumatoid arthritis (RA) (Stage I, Class 2) was made on the basis of gait disturbance, arthralgia persisting for more than 6 weeks, the presence of subcutaneous nodules and X-ray findings. CML was confirmed by peripheral blood and bone marrow findings and the presence of the Philadelphia chromosome and bcr gene rearrangement. High fever and dyspnea developed suddenly 3 days after administration of interferon in May 1991. In addition to pneumonia, a leucostasis was suspected and he was treated with high dose steroids and antibiotics. After improvement, the steroids were tapered and he was discharged from hospital in July 1991.